Improving Traffic Safety Through Innovation: A Systematic Review of Technology-Enhanced Education for Novice Drivers with Implications for LMICs - Dina Lusiana Setyowati; Yuliani Setyaningsih; Chriswardani Suryawati; Daru Lestantyo (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2026)
Introduction: Road traffic accidents remain a major global public health challenge, disproportionately affecting low- and middle-income countries (LMICs), where fatality rates among novice drivers are particularly high. Despite this burden, most empirical research on road safety education has focused on high-income settings, leaving significant gaps in evidence relevant to LMIC contexts. This study aims to systematically review the effectiveness of technology-based interventions for road safety education among novice drivers and to examine their behavioral outcomes, theoretical foundations, and contextual relevance in LMICs. Methods: A systematic literature review was conducted in accordance with PRISMA 2020 guidelines. Peer-reviewed journal articles published between 2015 and 2025 were retrieved from the Scopus database using predefined search terms related to road safety education, novice drivers, and digital or technology-enhanced interventions. After screening and eligibility assessment, 47 empirical studies were included for synthesis. Data were extracted on intervention type, theoretical framework, geographic setting, and behavioral outcomes, and analyzed using descriptive, thematic, and network-based approaches. Results: The findings indicate that technology-enhanced interventions, including gamification, virtual reality, mobile applications, telematics, and artificial intelligence, are generally associated with improved learner engagement, enhanced hazard perception, safer driving behavior, increased helmet use, and reduced traffic violations among novice drivers. However, most studies lack explicit theoretical grounding, rely on short-term outcome measures, and are concentrated in high-income settings, limiting generalizability to low- and middle-income contexts. Conclusion: This review highlights the need for theory-informed, culturally sensitive, and context-responsive road safety education strategies that integrate behavioral science with digital innovation. Strengthening longitudinal evaluation and expanding research in underrepresented regions are essential to inform effective policy and scalable intervention design.